Consider a subspace V of ℝ n with a basis v → 1 , ... , v → m ; supposewe wish to find a formula for the orthogonal projection onto V. Using the methods we havedeveloped thus far, we can proceed in two steps:We use the Gram-Schmidt process to construct anorthonormal basis v → 1 , ... , v → m of V, and then weuse Theorem 5.3.10: The matrix of the orthogonal projection is Q Q T , where Q = [ u → 1 ⋯ u → m ] . In this exercise we will see how we can write the matrix of the projection directly in terms of the basis v → 1 , ... , v → m and the matrix A = [ v → 1 ... v → m ] . (This issue will be discussed more thoroughly in Section 5.4; see Theorem 5.4.7.) Since proj V x → is in V. we can write proj V x → = c 1 v → 1 + ⋯ + c m v → m for some scalars c 1 , ... c m , yet to be determined. Now x → − p r o j V ( x → ) = x → − c 1 v → 1 − ⋯ c m v → m is orthogonal to V, meaning that v → i ⋅ ( x → − c 1 v → 1 − ⋯ − c m v → m ) = 0 for i = 1 , ... , m . a. Use the equation v → i ⋅ ( x → − c 1 v → 1 − ⋯ − c m v → m ) = 0 to show that A T A c → = A T x → , where c → = [ c 1 ⋮ c m ] . b. Conclude that c → = ( A T A ) − 1 A T x → and proj V x → = A c → = A ( A T A ) − 1 A T x → .
Consider a subspace V of ℝ n with a basis v → 1 , ... , v → m ; supposewe wish to find a formula for the orthogonal projection onto V. Using the methods we havedeveloped thus far, we can proceed in two steps:We use the Gram-Schmidt process to construct anorthonormal basis v → 1 , ... , v → m of V, and then weuse Theorem 5.3.10: The matrix of the orthogonal projection is Q Q T , where Q = [ u → 1 ⋯ u → m ] . In this exercise we will see how we can write the matrix of the projection directly in terms of the basis v → 1 , ... , v → m and the matrix A = [ v → 1 ... v → m ] . (This issue will be discussed more thoroughly in Section 5.4; see Theorem 5.4.7.) Since proj V x → is in V. we can write proj V x → = c 1 v → 1 + ⋯ + c m v → m for some scalars c 1 , ... c m , yet to be determined. Now x → − p r o j V ( x → ) = x → − c 1 v → 1 − ⋯ c m v → m is orthogonal to V, meaning that v → i ⋅ ( x → − c 1 v → 1 − ⋯ − c m v → m ) = 0 for i = 1 , ... , m . a. Use the equation v → i ⋅ ( x → − c 1 v → 1 − ⋯ − c m v → m ) = 0 to show that A T A c → = A T x → , where c → = [ c 1 ⋮ c m ] . b. Conclude that c → = ( A T A ) − 1 A T x → and proj V x → = A c → = A ( A T A ) − 1 A T x → .
Solution Summary: The author explains that the matrix of the orthogonal projection is QQT.
Consider a subspace V of
ℝ
n
with a basis
v
→
1
,
...
,
v
→
m
; supposewe wish to find a formula for the orthogonal projection onto V. Using the methods we havedeveloped thus far, we can proceed in two steps:We use the Gram-Schmidt process to construct anorthonormal basis
v
→
1
,
...
,
v
→
m
of V, and then weuse Theorem 5.3.10: The matrix of the orthogonal projection is
Q
Q
T
, where
Q
=
[
u
→
1
⋯
u
→
m
]
. In this exercise we will see how we can write the matrix of the projection directly in terms of the basis
v
→
1
,
...
,
v
→
m
and the matrix
A
=
[
v
→
1
...
v
→
m
]
. (This issue will be discussed more thoroughly in Section 5.4; see Theorem 5.4.7.) Since
proj
V
x
→
is in V. we can write
proj
V
x
→
=
c
1
v
→
1
+
⋯
+
c
m
v
→
m
for some scalars
c
1
,
...
c
m
, yet to be determined. Now
x
→
−
p
r
o
j
V
(
x
→
)
=
x
→
−
c
1
v
→
1
−
⋯
c
m
v
→
m
is orthogonal to V, meaning that
v
→
i
⋅
(
x
→
−
c
1
v
→
1
−
⋯
−
c
m
v
→
m
)
=
0
for
i
=
1
,
...
,
m
. a. Use the equation
v
→
i
⋅
(
x
→
−
c
1
v
→
1
−
⋯
−
c
m
v
→
m
)
=
0
to show that
A
T
A
c
→
=
A
T
x
→
, where
c
→
=
[
c
1
⋮
c
m
]
. b. Conclude that
c
→
=
(
A
T
A
)
−
1
A
T
x
→
and
proj
V
x
→
=
A
c
→
=
A
(
A
T
A
)
−
1
A
T
x
→
.
Need a deep-dive on the concept behind this application? Look no further. Learn more about this topic, algebra and related others by exploring similar questions and additional content below.